Foreign Experience in Increasing the Attractiveness of Financial Statements - Anvar Ziyadullayevich Avlokulov; Makhmudova Sharifa Elmurodovna (International Journal on Economics, Finance and Sustainable Development, 2022)
In the article given the procedure for drawing of the financial statements based on international standards, the possibility of analysis of the income statement and the prospects for their use in the practice of enterprises in Uzbekistan.